Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3189/2014jog13j119
|View full text |Cite
|
Sign up to set email alerts
|

21st-century increase in glacier mass loss in the Wrangell Mountains, Alaska, USA, from airborne laser altimetry and satellite stereo imagery

Abstract: Alaskan glaciers are among the largest regional contributors to sea-level rise in the latter half of the 20th century. Earlier studies have documented extensive and accelerated ice wastage in most regions of Alaska. Here we study five decades of mass loss on high-elevation, land-terminating glaciers of the Wrangell Mountains (~ 4900 km2) in central Alaska based on airborne center-line laser altimetry data from 2000 and 2007, a digital elevation model (DEM) from ASTER and SPOT5, and US Geological Survey topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 42 publications
(79 reference statements)
1
38
1
Order By: Relevance
“…This association of thinning, retreat, and acceleration at these particular glaciers suggests that dynamic changes are tied to variations in mass loss from marineterminating glaciers on the Stikine Icefield, particular near the fronts of these glaciers Several previous studies have noted that the largest error on the mass loss inferred from LIDAR studies is the extrapolation from limited observations to the entire area (e.g., Das et al, 2014) and the need for more complete sampling (e.g., Larsen et al, 2015). Our work confirms that at least over the Stikine Icefield, the expanded and continued LIDAR acquisitions and stereo-imaging over the glaciers that were not included in Larsen et al (2015) is essential for a complete picture of the mass loss.…”
Section: Discussionmentioning
confidence: 99%
“…This association of thinning, retreat, and acceleration at these particular glaciers suggests that dynamic changes are tied to variations in mass loss from marineterminating glaciers on the Stikine Icefield, particular near the fronts of these glaciers Several previous studies have noted that the largest error on the mass loss inferred from LIDAR studies is the extrapolation from limited observations to the entire area (e.g., Das et al, 2014) and the need for more complete sampling (e.g., Larsen et al, 2015). Our work confirms that at least over the Stikine Icefield, the expanded and continued LIDAR acquisitions and stereo-imaging over the glaciers that were not included in Larsen et al (2015) is essential for a complete picture of the mass loss.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, calibration and evaluation of the model were performed using observations of runoff from USGS stream gauges, satellite-based observations of ET (MOD16) [24] snow extent (MOD10CM) [23], and GRACE-derived estimates of total storage change, and by comparing glacier mass balance change to values reported in the scientific literature by Larsen et al [42], Arendt et al and Das et al [43]. In the present study, the additional evaluation of the first 11 years of simulations to observed runoff and GRACE storage was also successful.…”
Section: Discussionmentioning
confidence: 99%
“…Kääb, 2008;Nuth and Kääb, 2011;Das et al, 2014). To estimate the recent mass balance for TNIC, we used a DEM (product AST14DMO) generated from an ASTER stereo pair acquired on 3 August 2007.…”
Section: Aster Demmentioning
confidence: 99%